Assessment of photovoltaic generation, supply, and sustainability: a case study of municipalities in São Paulo state - Martin, Nilo Amaral [UNESP]; Germano Martins, Antônio Cesar [UNESP] (Editora de Livros IABS, 2021)
Energy consumption has been increasing together with population growth and the consequences for energy production widely generate discussions under the aspect of environmental outcome and supply reliability and quality. This paper proposes a methodology that allows the estimation of the potential for cities to be more independent in terms of centralized generation and distribution of electricity considering photovoltaic sources. Sustainability and environmental performance are also discussed. The methodology aims to assess some municipalities in the São Paulo state. The results showed high potential for photovoltaic supply in those municipalities under the considered conditions indicating the possibility for structuring a decentralized generation model where cities would be more independent in electricity supply. Implementing the required photovoltaic systems would return the energy consumed during their life cycle in a relatively short period compared to their expected lifetime.
Análise de potencial de geração e suprimento fotovoltaicos e sustentabilidade: estudo de caso de municípios do estado de São Paulo
Keywords: Distributed generation; Modelling; Photovoltaic generation; Sustainability; Sustainable energy